UJI EFEKTIVITAS EKSTRAK ETANOL DAUN KELOR (MORINGA OLEIFERA L) TERHADAP PENURUNAN KADAR KOLESTEROL DARAH PADA MENCIT (MUS MUSCULUS) JANTAN - Mukhriani Mukhriani; Nurlina Nurlina; Andi Nilan; Afrisusnawati Rauf (Universitas Islam Negeri Alauddin Makassar, 2014)
Test of efficacy studies have been conducted leaf extract (Moringa oleifera L) to decrease blood cholesterol levels in mice (Mus musculus) males. This study aims to determine the effectiveness of moringa leaf extract on reducing cholesterol in mice. In this study using 15 male mice were divided into 5 groups. Before being given treatment, mice were first fasted for 8 hours and then measured cholesterol levels initially. After that induced propylthiouracil every day on each mouse to raise the cholesterol levels of mice for 14 days. Furthermore, given the different treatments in each group for 14 days and total cholesterol levels were measured on day 28th Group I was given NaCMC 1% w / v as a negative control and the obtained yield was 150 mg / dL, 183 mg / dL and 254 mg / dl, group II was given a suspension Simvastatin as a positive control and the results obtained 136 mg / dL, 155 mg / dL, and 164 mg / dL, a group III, IV, and V are given extracts of leaves (Moringa oleifera L) with three variations of the dose 50 mg / g, 100 mg / g, 200 mg / g and the results obtained successively by 127 mg / dL, 135 mg / dL, 152 mg / dL, 170 mg / dL, 176 mg / dL, 188 mg / dL, 156 mg / dL, 137 mg / dL, 175 mg / dL. The results showed that the leaf extract of Moringa can lower total cholesterol levels of mice at a dose of 200 mg / g, but not as effective as simvastatin.